A rare case of non-typhi salmonella meningitis in an immunocompetent adult: a case study - Sunnan, Moinuddin; Batukbhai, Bhalala Priyank; Ribadiya, Fenilkumar Nitinbhai; Sadadiwala, Mehul Hitesh (International Journal of Research in Medical Sciences, 2024)
Salmonella, a gram-negative motile bacillus, is commonly associated with typhoid fever, septicemia, and diarrhea. Non-typhi Salmonella (NTS) can cause bacteremia, meningitis, focal septic infections, pneumonia, and osteomyelitis, although NTS meningitis is rarely reported in immunocompetent adults and is more common in immunocompromised patients, infants, and children. NTS infections are typically transmitted through contaminated food or water, and clinical presentations often lack specific symptoms, making diagnosis challenging. Due to the higher mortality rates, aggressive management with proper antibiotic susceptibility testing is advised. The risk of antibiotic resistance, recurrence, and the invasive nature of the infection make early diagnosis and treatment crucial. The treatment approach should be guided by performing proper antibiotic sensitivity testing. The higher risk of complications, including hydrocephalus, seizures, and empyema, highlights the importance of close follow-up. We describe a case of NTS meningitis that possibly occurred after the consumption of guinea pig meat, where early presentation and appropriate management led to a favorable outcome without progression to further complications.